Strategi Kreavoks dalam Mengembangkan Jasa Digital untuk Mempersiapkan Generasi Muda Menghadapi Industri 4.0 - Setiady Ibrahim Anwar; Hafiz Fadli Faylasuf; Muhammad Alwan Ataya; Wien Kuntari (Jurnal Bisnis Kreatif dan Inovatif, 2024)
With the growth of technological innovation and the shift of the digital era in various aspects of industry, the younger generation is faced with major challenges in preparing themselves for the technology-based world of work. This study focuses on Kreavoks, a digital agency that provides services such as digital skills training, SEO-optimized website creation, and branding kit design. The purpose of this study is to explore how Kreavoks develops its digital services to prepare the younger generation with the skills needed to face the challenges of Industry 4.0. Using a qualitative descriptive approach, this study analyzes the strategies implemented by Kreavoks in integrating technology, branding, and marketing to improve the digital capabilities of the younger generation. The research findings show that Kreavoks' training program improves participants' technical skills and deepens their understanding of digital branding and SEO. Despite its success, challenges such as differences in technological understanding and limited infrastructure remain obstacles. This study has an impact on the development of digital services that can prepare the younger generation to face the demands of Industry 4.0.